2019
DOI: 10.1371/journal.pone.0210059
|View full text |Cite
|
Sign up to set email alerts
|

Topical essential fatty acid oil on wounds: Local and systemic effects

Abstract: BackgroundThe use of medicinal plants and their derivatives is increasing, and approximately one-third of all traditional herbal medicines are intended for wound treatment. Natural products used in these treatments include vegetable oils, which are rich in essential fatty acids. Once in contact with an ulcerative surface, the oil reaches the blood and lymphatic vessels, thus eliciting systemic effects.ObjectiveThis study evaluated the local and possible systemic effects of essential fatty acids (sunflower oil)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
(50 reference statements)
0
16
0
4
Order By: Relevance
“…The use of medicinal plants and their derivatives is increasing, and approximately one-third of all traditional herbal medicines are intended for wound treatment [ 22 ]. Due to the facility to obtain and the desirable physicochemical properties, oils are one of the most common medicinal preparations used in traditional medicine around the world.…”
Section: Resultsmentioning
confidence: 99%
“…The use of medicinal plants and their derivatives is increasing, and approximately one-third of all traditional herbal medicines are intended for wound treatment [ 22 ]. Due to the facility to obtain and the desirable physicochemical properties, oils are one of the most common medicinal preparations used in traditional medicine around the world.…”
Section: Resultsmentioning
confidence: 99%
“…A capacidade dos AGE que compõem o OG para promover o processo cicatricial em feridas tem sido pesquisada desde 1929. Atualmente, o OG é um dos produtos mais utilizados na pratica clínica para o tratamento e prevenção de feridas, visto que o óleo é rico em AGE e foi aprovado pela Agência Nacional de Vigilância Sanitária (Anvisa) como curativo, no entanto, poucos estudos discutem sua capacidade antibacteriana (Mota et al, 2015;(Lania, et al, 2019;Saturno, et al, 2017).…”
Section: Discussionunclassified
“…Os ácidos graxos essenciais (AGE) são produtos muito utilizados na prática clínica para o tratamento de feridas, tais como úlceras de pressão, neuropatias venosas e arteriais, queimaduras, deiscências cirúrgicas, entre outras, por apresentarem baixo custo, fácil acesso e ser um agente cicatrizante (Lania, et al, 2019;Tran, et al, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The addition of RPLO to human fibroblast cultures increased the cell migration rate compared to the control treatment. An increased fibroblast migration rate was also observed after supplementation of the medium with a mixture of vegetable oils [ 50 ]. In addition to the positive effects on the migration rate of fibroblasts, Guidoni et al [ 51 ] observed that a mixture of vegetable oils promoted an inflammatory response controlled by the modulation of the levels of pro-inflammatory mediators and cytokines (TNF-α and IL-6).…”
Section: Discussionmentioning
confidence: 99%